Adsorption characteristics of tetracycline onto particulate polyethylene in dilute aqueous solutions. (15th September 2021) - Nguyen, Thanh-Binh; Ho, Thi-Bao-Chau; Huang, Chin-Pao; Chen, Chiu-Wen; Hsieh, Shu-Ling; Tsai, Wen-Pei; Dong, Cheng-Di
Abstract: The presence of ultrafine plastics particles and its potential to concentrate and transport organic contaminants in aquatic environments have become a major concern in recent years. Specifically, the uptake of hazardous chemicals by plastics particles may affect the distribution and bioavailability of the chemicals. In this study, the adsorption of tetracycline (TC), an antibiotic frequently found in aquatic environments, on high-density polyethylene (PE) particles with the average size of 45 μm, was investigated. The PE particles were characterized for surface acidity for the first time. Results showed that pH controls the surface charge of PE particles. TC adsorption onto PE particles was rapid as expected following the pseudo-second-order rate law (r 2 > 0.99). Polar forces in addition to specific chemical interactions, such as hydrogen bonding and hydrophophilicity controlled TC adsorption onto PE particles. Parameters, including pH, dissolved organic matter, ionic strength, major cations and anions affected TC adsorption onto PE micro-particles. Results indicated that PE particles can function as a carrier of antibiotics in the aquatic environment, which potentially imposes ecosystem and human health risks. Graphical abstract: Image 1 Highlights: Surface acidity of PE particles, i.e., strength and capacity, was determined. pH was potential-determining ion controlling the surface charge of PE particles. TC adsorption followed the pseudo-second-order kinetics model (R 2 > 0.99). Stability constants for bidentated surface complexes were determined. Specific chemical adsorption played a major role on TC adsorption. Abstract : PE particles exhibit function as a carrier of antibiotics in the aquatic environment, which potentially imposes ecosystem and human health risks.